Key questions on patent disclosure requirements for genetic resources and traditional knowledge, 2020 (WIPO Publication, 2020)
Policymakers and other stakeholders often raise operational questions and seek practical and empirical information about patent disclosure requirements in relation to genetic resources and traditional knowledge. This authoritative study offers a comprehensive and scrupulously neutral overview of key legal and operational questions arising within this context. Los formuladores de políticas y otras partes interesadas a menudo plantean cuestiones operativas y buscan información práctica y empírica sobre los requisitos de divulgación de patentes en relación con los recursos genéticos y los conocimientos tradicionales. Este estudio autorizado ofrece una visión global y escrupulosamente neutral de las principales cuestiones jurídicas y operativas que surgen en este contexto.